2008
DOI: 10.1002/mawe.200800271
|View full text |Cite
|
Sign up to set email alerts
|

Processing and property assessment of NiTi and NiTiCu shape memory actuator springs

Abstract: Among the multifarious engineering applications of NiTi shape memory alloys (SMAs), their use in actuator applications stands out. In actuator applications, where the one-way effect (1WE) of NiTi SMAs is exploited, SM components are often applied as helical coil springs. Ingots are generally used as starting materials for the production of springs. But before SM actuator springs can be manufactured, the processing of appropriate wires from NiTi ingots poses a challenge because cold and hot working of NiTi SMAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 23 publications
2
54
0
Order By: Relevance
“…After the final deformation step, the wires were straightened and again subjected to RA. Our procedure establishes a fully recrystallized microstructure with a medium grain size close to 30 lm [45,46]. The resulting NiTi wires were used for all subsequent mechanical tests, where the processing stress/strain history was no longer considered and the deformation of the asprocessed material was reset to u = 0.…”
Section: Experimental Procedures Production Of Tie Wiresmentioning
confidence: 99%
See 1 more Smart Citation
“…After the final deformation step, the wires were straightened and again subjected to RA. Our procedure establishes a fully recrystallized microstructure with a medium grain size close to 30 lm [45,46]. The resulting NiTi wires were used for all subsequent mechanical tests, where the processing stress/strain history was no longer considered and the deformation of the asprocessed material was reset to u = 0.…”
Section: Experimental Procedures Production Of Tie Wiresmentioning
confidence: 99%
“…Wires with diameters of 1.66, 1.6, 1.54, 1.44, 1.34, and 1.25 mm (corresponding to pre-deformation levels of u = 0.07, 0.14, 0.22, 0.35, 0.49, and 0.63) were thus obtained. All further details on thermomechanical treatments are given elsewhere [21,[45][46][47].…”
Section: Experimental Procedures Production Of Tie Wiresmentioning
confidence: 99%
“…In order to design new SMAs possessing very small transformation temperature hysteresis, understanding the effect of alloying on martensite structures is of vital importance. Previously reported works have studied the effects of Cu content on transformation temperature [10], microstructure [7,8,11,12], stress-strain characteristic and fatigue life [13][14][15], as well as applications as actuators [5,16]. Earlier research has found that the Cu content in TiNiCu alloys has little influence on the MT temperature but obvious effect on the MT pathway [11,12,17].…”
Section: Introductionmentioning
confidence: 99%
“…Gil et al [14,15] showed that NiTiCu SMAs exhibit a much more narrow stress hysteresis, based on transformation stresses, as compared to binary NiTi SMAs. Fatigue testing of NiTiCu SMA actuator springs were conducted by Grossmann et al [16,17]. They reported that the functional fatigue resistance of NiTiCu SMAs is strongly improved by the addition of Cu.…”
Section: Introductionmentioning
confidence: 99%
“…Sehitoglu et al [18,19] and Biscarini et al [20] investigated the mechanical properties of NiTiCu single crystal SMAs under compression loading, and reported that the slip resistance increases when Ni-rich precipitates are present. To date, the mechanical behavior of bulk NiTiCu SMA is well established [7,[14][15][16][17][18][19][21][22][23][24]; however, few studies have focused on the effect of porosity on NiTiCu SMAs [25][26][27][28]. Goryczka et al [26,27] examined powder processing methods for producing homogenous NiTiCu SMAs.…”
Section: Introductionmentioning
confidence: 99%